Balance of Loyalties: Explaining Rebel Factional Struggles in the Nicaraguan Revolution. (20th October 2019) - Mosinger, Eric S.
Abstract: What explains the causes and outcomes of rebel factional struggles? Existing explanations focus on exogenous and material factors that disrupt rebel organizations' internal processes. Yet rebel groups succumb to infighting and organizational splinters even in the absence of external shocks. In this article I present an endogenous and social theory of rebel factional struggles, in which leadership disputes result from a shifting balance of loyalties within a rebel organization. In my model, rival rebel leaders cultivate the loyalty of two types of networks, recruitment networks and operational networks, which serve as power bases to initiate leadership struggles, launch coups, or split organizations. I build my theory through a case study of Nicaragua's Frente Sandinista de Liberación Nacional (FSLN), which splintered into three factions in 1975–76. Drawing on an original network dataset of FSLN commanders, I trace how the organization's network structure changed over time, spurring disputes over rank-and-file fighters' loyalties that tore the FSLN apart.